External experts' integration into educational processes at university - Šuligoj, Metod (Raziskave in razprave, 2014)
Tourism education at universities tends to focus on qualifying students for future careers in tourism. Little attention has been devoted to the introduction of external experts into the educational process and the quality of their work at universities. This paper attempts to promote the awareness of educational quality of professional and non-professional teachers (external experts). A revised version of the Course Experience Questionnaire (CEQ) was administered to students at a faculty in Slovenia. The results suggest that the CEQ demonstrated a good internal consistency. Further, we determined that with most items there are no statistical significant differences between professional and non-professional teachers. Limitations of and directions for future research are discussed as well.
Keywords: tourism; turizem; tourism education; education; izobraževanje; učitelji; teachers; zunanji strokovnjaki; external experts; CEQ; quality; kakovost